Dry friction behaviour of a geosynthetic interface using inclined plane and shaking table tests. Issue 4 (August 2015) - Carbone, L.; Gourc, J.P.; Carrubba, P.; Pavanello, P.; Moraci, N.
Abstract Inclined plane test is widely used, especially in Europe, for the friction characterization of geosynthetics liner systems, for example in landfill applications. However, interpretation of the test is more complex and less consensual than for the direct shear test. In this paper, a comprehensive analysis of interface behaviour at the Inclined Plane device is presented for a non-woven geotextile on a geomembrane in dry condition. New test procedure are proposed, and the related parameters of friction are defined in order to properly characterise friction behaviour. For the Inclined Plane, the shear strength of a geosynthetic interface cannot be characterised by a single parameter, as the interface behaviour is sensitive to the different kinematic conditions. To this purpose, a comparison is shown with the results of complementary tests carried out using the Shaking Table test. For both test procedures, particular attention was paid to the influence of the relative sliding velocity. Finally, the sensitivity of the interface to mechanical damage caused by large relative displacements was quantified.